Conduit dynamics and post explosion degassing on Stromboli: A combined UV camera and numerical modeling treatment - T. D. Pering; A. J. S. McGonigle; M. R. James; G. Tamburello; A. Aiuppa; D. Delle Donne; M. Ripepe (Geophysical Research Letters)
Abstract Recent gas flux measurements have shown that Strombolian explosions are often followed by periods of elevated flux, or “gas codas,” with durations of order a minute. Here we present UV camera data from 200 events recorded at Stromboli volcano to constrain the nature of these codas for the first time, providing estimates for combined explosion plus coda SO2 masses of ≈18–225 kg. Numerical simulations of gas slug ascent show that substantial proportions of the initial gas mass can be distributed into a train of “daughter bubbles” released from the base of the slug, which we suggest, generate the codas, on bursting at the surface. This process could also cause transitioning of slugs into cap bubbles, significantly reducing explosivity. This study is the first attempt to combine high temporal resolution gas flux data with numerical simulations of conduit gas flow to investigate volcanic degassing dynamics.